A Software Re-engineering Perspective of a Development Process : Case Korpi ForRest - Hilanne, Tommi (My University, 2021)
Software re-engineering is about taking an existing system and examining it or making changes to it in order to improve it. User experience is about a user’s observable and measurable interaction with a system. Usability on the other hand is about the functional aspects of user experience. Usability can be measured with metrics, and usability studies can be conducted to gain insights of some particular project. The company Korpi ForRest is developing an audiovisual digital forest experience that can be used to de-stress during work breaks. The company follows Lean Startup methodologies, in other words they aim to build their product iteratively in a customer data driven way. This thesis aims to review the development process of Korpi ForRest’s solution from the perspective of software re-engineering, as well as user experience and usability. The goal is to inspect whether software re-engineering methods are applicable in a lean startup context, and how usability measurement affects them. The process review consists of investigating the development processes of the company by leveraging established literature on the subject, and inspecting different options for the future development of the solution. Additionally, a usability study was conducted on one of the company’s earlier versions of their solution. The process review and case study found that software re-engineering methods can be used to effectively analyze and model software development processes. Aspects of user experience and usability also have an effect on the re-engineering.
Keywords: software re-engineering, abstraction, alteration, refinement, user experience, usability, usability metrics, proof of concept, lean startup